Unveiling Baghdad's Urban Identity: A Comprehensive Study on the Dynamics of Urban Imprint - Asawer Abdulrahman Abbas; Shaimaa Hameed Hussein (Universitas Muhammadiyah Sidoarjo, 2024)
This research examines the